Ruptured anterior communicating artery aneurysms treated by Coiling technique: Characteristics, Outcomes, and Prognoses - Tran , Nguyen Tuan Minh; Le Huynh Vu, Le Nguyen Ngoc Minh, Nguyen Thi Ngoc Tran, Nguyen Thi Nhan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
A prospective study of 31 patients with ruptured anterior communicating artery aneurysm (ACoA) treated by endovascular coiling was carried out at the Stroke Center - Hue Central Hospital, from September 2018 to February 2020. The results obtained were: Male: female ratio = 2.1: 1, age 54.2 ± 15.3 (21-85); clinically sudden onset 100%, headache 87.1%, vomiting 45.2%, cranial nerve palsy 12.9%, hemiparesis 29%, aphasia 11%; Hunt-Hess 1-3 61.3%, Fisher 1-3 35.2%, Glasgow coma score ≤8 19.4%; aneurysm size 5.6 ± 2.0 mm (2.5-10 mm), complete obliteration 81%; delayed ischemia 19.4%, ventricular dilation 45.2%, in-hospital recurrent hemorrhage 0%, modified Rankin scale (mRS) 0-2 at discharge 51.6%; mRS 0-2 after 3 months 54.8%, in-hospital death 0%, death within 3 months 22.6%. There was a moderate correlation between Hunt-Hess, Glasgow score at admission and mortality within 3 months; there was a statistically significant relationship between Glasgow coma scale-based groups and mortality (OR 0.34; 95% CI: 0.12 - 0.99; p = 0.047, p-value 77.4%).